Joaquim Nogueira: percurso profissional, projetos escolares e práticas educacionais (1904-1934) - Bezerra, Daniele Barbosa (2015)
Joaquim da Costa Nogueira was dedicated to education in Fortaleza in the 1904-1934 period. He founded the Institute of Humanities (1904) and the Collegio Nogueira (1918) who were in the history of Ceará education by forefront of their educational experience. This research reconstructs his career, school and educational projects supported by it; identifies theorists that underpinned in your professional life as well as the readings as guidelines in the construction of knowledge. The sum with your educator activity presents itself, another facet of Joaquim Nogueira, the books editor. Owner of Typhographia School, next to his son, José Mendonça Nogueira, were responsible for several didactic publications, as well as other genres, such as the School Magazine, the Anno School, the Deck Arithmético, The Progressive Lessons from the First Letters, Lessons Arithmética, the Cearense Yearbook; the newspaper, Bandeirante; the Miscellanea, the Cearense Indicator, the journal Bric à Brac. In addition, it identifies the supporting characters of his story, in chain of sociability, until then, remain ignored by historiography. Dialogue with size of the authors of Ricoeur, Le Goff, Dosse, Wolff, Veyne, were instrumental in the construction of this research. The relevance of this biography to the history of education is due to the possibility of understanding of their educational practices, and the need to place him in the company of the first three decades, Ceará, from professional ties with educators and intellectuals from other states and countries. It concludes that the name of Joaquim da Costa Nogueira is extremely important for the history of education in Ceará and can not be ignored by researchers in the field. Keywords: Biography of Joaquim da Costa Nogueira. Pedagogical practices. Cearense education. Chain of sociability.